Cellular agriculture in the UK: a review [version 2; peer review: 2 approved, 2 approved with reservations] - Neil Stephens; Marianne Ellis (Wellcome Open Research, 2020)
This review details the core activity in cellular agriculture conducted in the UK at the end of 2019, based upon a literature review by, and community contacts of the authors. Cellular agriculture is an emergent field in which agricultural products—most typically animal-derived agricultural products—are produced through processes operating at the cellular level, as opposed to (typically farm-based) processes operating at the whole organism level. Figurehead example technologies include meat, leather and milk products manufactured from a cellular level. Cellular agriculture can be divided into two forms: ‘tissue-engineering based cellular agriculture’ and ‘fermentation-based cellular agriculture’. Products under development in this category are typically valued for their environmental, ethical, and sometimes health and safety advantages over the animal-derived versions. There are university laboratories actively pursuing research on meat products through cellular agriculture at the universities of Bath, Newcastle, Aberystwyth, and Aston University in Birmingham. A cellular agriculture approach to producing leather is being pursued at the University of Manchester, and work seeking to produce a palm oil substitute is being conducted at the University of Bath. The UK cellular agriculture companies working in the meat space are Higher Steaks, Cellular Agriculture Ltd, CellulaRevolution, Multus Media and Biomimetic Solutions. UK private investors include CPT Capital, Agronomics Ltd, Atomico, Backed VCs, and Breakoff Capital. The UK also has a strong portfolio of social science research into diverse aspects of cellular agriculture, with at least ten separate projects being pursued over the previous decade. Three analyses of the environmental impact of potential cellular agriculture systems have been conducted in the UK. The first dedicated third-sector group in this sector in the UK is Cultivate (who produced this report) followed by Cellular Agriculture UK. International groups New Harvest and the Good Food Institute also have a UK presence.